The role of national governance systems in biofuel development: a comparative analysis of lessons learned - Schoneveld, George C.; German, L.; Andrade, R.; Chin, M.; Caroko, W.; Romero Hernández, O. (Center for International Forestry Research, 2010)
Governments have played only a marginal role in the development of the biofuels market in most developing countries. For biofuel development to contribute to domestic energy security objectives, considerable initial financial support may be required. Biofuel production for domestic or underregulated export markets may contribute to environmental degradation, given the poor performance of feedstock cultivation in environmental impact assessments. Investment liberalisation and the lack of formal mechanisms to enhance smallholder participation indicate that benefits from biofuel development will likely be highly concentrated. The expansion of large-scale biofuel plantations could limit traditional land users’ access to resources due to ineffective governance. Poor enforcement—rather than absence— of existing regulatory safeguards is one of the main constraints to sustainable biofuel development.